Metal oxide supported iron-nickel nano-alloys in the reverse water-gas shift reaction - De Kock, Karina (Department of Chemical Engineering, 2024)
Rising atmospheric CO2 concentrations pose an existential threat to human life. The development of carbon capture and utilization (CCU) technologies which can consume CO2 at the same scale that it's being produced are necessary to limit the global mean surface temperature increase to 2 °C, in accordance with the Paris Agreement. A challenge in developing these technologies is to activate CO2, which is thermodynamically low in energy and needs to be reacted with high energy molecules. The Power-to-X (PtX) concept considers various pathways and technologies for the conversion of CO2 to different target products. PtX assumes the availability of cheap renewable energy and green H2 in the future and in many of these scenarios, CO2 is first activated to carbon monoxide via the reverse water- gas shift (RWGS) reaction. The RWGS is thermodynamically limited. CO and CO2 methanation are favoured over the RWGS at industrially preferred reaction conditions and there is a need for low temperature catalysts with a high CO selectivity. Noble metal catalysts have been well studied for the RWGS, though affordable and abundant metals are required for large-scale applications. Iron-based catalysts have been widely explored due to their high stability, while nickel catalysts are rarely considered for the RWGS due to their known hydrogenation activity. Metal oxide (MOx) catalysts, such as ceria, have also been studied for the RWGS due to their high oxygen storage capacity and reducibility at high temperatures. In recent work from the group of Fischer at the University of Cape Town, supported Fe-Ni nanoparticles showed promising CO2 activation potential. It was found that upon reduction of the oxidic Fe-Ni precursor nanoparticles, a mixture of fcc and bcc alloy phases was formed. An increase in Fe content increased the concentration of the bcc phase in the alloy. It was further demonstrated that the bcc surface of the Fe-Ni alloy activates CO2 while the fcc surface of the alloy appears to be inert. This work further studies the FexNiy/MOx catalysts developed by the group of Fischer, which make use of novel synthesis approaches. The reducibility of two different MOx support materials is studied (M = Cr and Ga). To limit the effect of the varying physical properties of the respective bulk oxides on catalyst performance, bespoke support materials were prepared by impregnating a common γ-Al2O3 carrier with MOx overlayers. The surface of the prepared materials has the chemical and electronic properties of the respective MOx, but the pore geometry of the γ-Al2O3 is maintained. The effect of iron content on catalytic performance is of interest, and to obtain the Fe-Ni alloy phase, oxidic (NixFe1-x)Fe2O4 precursor nanoparticles of varying composition are synthesized (Fe:Ni = 3, 5 and 7, as well as pure iron oxide). This approach increases the chance of alloy formation upon reduction of the precursor particles compared to techniques such as co-impregnation, as the Fe and Ni are well mixed in the precursor particle. A hydrothermal synthesis technique in benzyl alcohol is employed to produce nanoparticles with a narrow size distribution without the use of surfactants, which are difficult to remove and can influence catalytic performance. The nanoparticles are deposited onto the two MOx@Al2O3 overlayer materials, as well as onto inert SiO2 to isolate the performance of the metallic Fe-Ni phases without support effects. Characterizations of the unsupported (NixFe1-x)Fe2O4 confirm that nanoparticles of varying composition are successfully synthesized in the correct phase with satisfactory overlap in particle size distribution. Characterizations of the prepared MOx@Al2O3 overlayer support materials confirm that the desirable textural properties of the underlying γ-Al2O3 support are maintained. No bulk MOx crystallites are detected, suggesting the MOx exists as a 2D overlayer covering the γ-Al2O3 surface. H2- TPR studies in in-situ XRD confirm that the reduced catalysts contain a mixture of a bcc alloy phase and an fcc alloy phase in agreement with the previous work and irrespective of the support material. The relative concentrations of each phase are a function of iron content, with an increase in iron content increasing the concentration of the bcc alloy phase. In-situ XRD temperature-programmed CO2 activation experiments confirm that the bcc phase has a high affinity towards re-oxidation but, unlike in the previous work, the fcc phase was found to be partially re-oxidized at elevated temperatures (> 600 °C). Catalytic performance evaluation was carried out in a dual quartz tube fixed-bed reactor set-up at 600 °C. All samples tested show > 99% CO selectivity but, using Fe100/SiO2 as a reference catalyst, it was found that alloying Fe with Ni and the use of an active support has significant impacts on catalytic activity and stability. The SiO2-supported samples all deactivated rapidly and in general, the CrOx- supported samples have the best activity, and the GaOx-supported samples have the best stability. Catalytic performance is dependent on both the alloy composition and the MOx support, with the surprising observation made of a reversal of the trend in activity with iron content between CrOx@Al2O3 and GaOx@Al2O3. Spent catalyst characterization showed that the rapid deactivation seen on SiO2 cannot be explained by sintering, oxidation, or carbon deposition. The deactivation is instead credited to the consumption of the bcc phase under reaction conditions. The results show that there is some interaction between the fcc phase and an active supports which enhances RWGS performance. Possible untested explanations for this could be enhanced H2 activation on the fcc phase which boosts CO2 activation on the support through a H+ spillover effect, or the creation of new active sites at the metal-metal oxide interface which are RWGS active.